Gratuitousness: Notes Towards an Anthropology of Interiority - Rapport, Nigel (The Australian journal of anthropology, 2008)
Interiority—an individual's inner consciousness, the continual conversation one has with oneself–remains an anthropological terra incognita. Literature has been less circumspect in this regard; fiction might be said to be ‘truer’ than social science in its efforts and intent to deal with how individual consciousness feels in the everyday and is immanent in social life. In this article I argue for recognising interiority as a crucial focus of anthropological endeavour, and I outline a possible way in which interiority might be evidenced as irrupting onto the social scene. Interiority makes its paradoxical appearance in social settings in the form of a strangeness, an individual purity and integrity, for which the term ‘gratuitousness’ is apposite. The language of individuals' interior conversation is routinely contained within the language of public exchange; on occasion it bursts these bounds. In both cases, I contend, interior conversation is an existential norm, which holds a key to understanding social life. The course of the article is to review, briefly but critically, disciplinary tendencies which have rendered individual interiority an impossible or irrelevant anthropological theme. A method of interiority is then outlined by way of an anthropological reading of two literary texts. The article ends by reconsidering the potential of an anthropology project that has a concern for interiority. The modern discovery of inner experience, of a realm of purely personal events that are always at the individual's command, and that are his exclusively as well as inexpensively for refuge, consolation and thrill is also a great and liberating discovery. It implies a new worth and sense of dignity in human individuality.